Fragilidade financeira, ciclo fiscal e crise municipal - Piorski, César Ricardo Leite (2020)
This work aims to propose an analytical approach that allows to address the phenomenon of the fiscal crisis at the municipal level. To this, the thesis arises that the fiscal cycle of the Union conditions the policy and fiscal balance of the municipalities, not because they depend heavily on external resources, but because of their budgetary economic structure — or the degree of financial fragility — that of non-observances in the budget allocation, accumulate imbalances between flows and stocks. Thus, in order to highlight the influence of the Union's fiscal cycle on the conditioning of the financial health of the municipalities, the Modern Monetary Theory (MMT) was used. Likewise, the financial condition of the municipality is analyzed from the Financial Fragility Hypothesis, Minsky (1992) together with the dynamic working capital model. From the integration of the financial fragility hypothesis, present in Minsky and the dynamic working capital model, it was possible to establish the micro foundations of financial fragility, which allows greater accuracy in the analysis of the financial situation of the municipal entity. Therefore, given that in the public sector the allocation of resources does not require the price system, the theory of production would not be of great value. Thus, in order to fill the existing gap, recourse to the (neo) institutionalist foundations, notably the subfield of transaction costs. problem of resource allocation within the scope of the municipal public sector, they are: i) cost-benefit method; ii) economic revenue method and, iii) data envelopment analysis. In order to validate such an analytical cut, the same was applied to the experience of the Curitiba Recovery Plan (PRC), whose content retains, to a large extent, the propositions discussed here. The results from the PRC allow us to state that the analytical approach proposed here proved to be so useful. Finally, from the SFC modeling, it was inferred the general laws of production, circulation and distribution of incomes (wages and profits) in an economy whose municipality enters a framework of financial crisis. From the SFC modeling, it was possible to identify the general laws of operation of a small economy in a context of financial crisis, which can be summarized as follows: i) there is a detachment of the local economy in relation to the national economy; ii) the share of private sector wages in income, increases at the expense of profits and the wages of the government sector; iii) the economy enters an ad continum imbalance, thereby losing its long-term trajectory.